2011
DOI: 10.1002/mus.22256
|View full text |Cite
|
Sign up to set email alerts
|

Altered β‐adrenergic response in mice lacking myotonic dystrophy protein kinase

Abstract: The protein kinase product of the gene mutated in myotonic dystrophy 1 (DMPK) is reported to play a role in cardiac pathophysiology. To gain insight into the molecular mechanisms modulated by DMPK, we characterize the impact of DMPK ablation in the context of cardiac β-adrenergic function. Our data demonstrate that DMPK knock-out mice present altered β-agonist-induced responses and suggest that this is due, at least in part, to a reduced density of β1-adrenergic receptors in cardiac plasma membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…As our analysis indicates, this regulation might include cis -acting regulatory elements in dissimilar neighboring genes, such as a muscle-specific enhancer for muscle-related upregulation of DMPK in the testis-specific RSPH6A gene. The tissue-specific epigenetics of DMPK that we have described is consistent with the importance of this gene to myoblast differentiation [ 3 ], insulin signaling in skeletal and cardiac muscles [ 4 ], regulation of ion channels in skeletal muscle [ 7 , 23 ], cardiac conduction [ 9 ], and with the much higher levels of DMPK protein in heart and skeletal muscle relative to most other tissues [ 79 ]. Last, the tissue-specific epigenetics in and around DMPK and the G-quadruplex motifs near the DM1-linked CTG repeat at the 3′ end of DMPK are likely to be important in understanding disease mechanisms for this highly lethal and debilitating disease.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As our analysis indicates, this regulation might include cis -acting regulatory elements in dissimilar neighboring genes, such as a muscle-specific enhancer for muscle-related upregulation of DMPK in the testis-specific RSPH6A gene. The tissue-specific epigenetics of DMPK that we have described is consistent with the importance of this gene to myoblast differentiation [ 3 ], insulin signaling in skeletal and cardiac muscles [ 4 ], regulation of ion channels in skeletal muscle [ 7 , 23 ], cardiac conduction [ 9 ], and with the much higher levels of DMPK protein in heart and skeletal muscle relative to most other tissues [ 79 ]. Last, the tissue-specific epigenetics in and around DMPK and the G-quadruplex motifs near the DM1-linked CTG repeat at the 3′ end of DMPK are likely to be important in understanding disease mechanisms for this highly lethal and debilitating disease.…”
Section: Discussionsupporting
confidence: 72%
“…The most prominent roles of DMPK protein in normal tissues are in skeletal and heart muscle. Its functions include regulating calcium ion homeostasis in myotubes (Mt) [ 6 ], sodium ion-channel gating in skeletal muscle tissue [ 7 ], promoting Mt formation from myoblasts (Mb) [ 8 ], protecting against age-related muscle weakness [ 1 ], protecting membrane-bound cardiac β-adrenergic receptors [ 9 ] and facilitating atrioventricular conduction [ 10 ]. Although DMPK is expressed in diverse tissues, skeletal muscle, cardiac muscle and certain smooth muscles display much higher steady-state levels than most other tissues [ 11–14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, 227 studies remained for the full-text analysis, in which 181 did not present relevant data for the aim of this review and four did not use DM1 biological models. Finally, 41 studies [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] were included in the present systematic review. The details of the screening process can be found in the PRISMA flow diagram in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic mice expressing the human skeletal actin gene with 250 CTG repeats (HSALR) was the most used mice model to study protein phosphorylation in DM1 (n = 4) [ 26 , 33 , 43 , 44 ] ( Figure 2 B). Further, the DMSXL mice (n = 3) [ 53 , 54 , 55 ], Dmpk knockout mice (n = 2) [ 38 , 39 ], and inducible transgenic mice with expanded repeats induced by Tamoxifen (TAM) (n = 2) [ 37 , 52 ] were also among the most used DM1 mice models ( Figure 2 B). Concerning the human samples, in most studies skeletal muscle biopsies were used (n = 15) [ 26 , 28 , 29 , 32 , 33 , 34 , 40 , 45 , 46 , 50 , 57 , 58 , 59 , 61 , 62 ], followed by primary myoblasts (n = 7) [ 24 , 31 , 33 , 47 , 49 , 50 , 53 ] and primary myotubes (n = 4) [ 25 , 28 , 47 , 49 ] ( Figure 2 C).…”
Section: Resultsmentioning
confidence: 99%
“…Conduction defects, like those of DM1 patients, such as age-dependent first-degree atrioventricular blocks, have been reported in heterozygous adult Dmpk knock-out mice [ 158 , 159 ]. Another study showed that there are fewer β1-adrenergic receptors at the cardiac sarcolemma of Dmpk knock-out mice, suggesting that DMPK protein plays a role in the regulation of membrane trafficking [ 160 ]. Dmpk knockout mice have also been reported to feature increased CELF phosphorylation and nuclear localization [ 161 ].…”
Section: Safety and Tolerability Of Dmpk -Targetin...mentioning
confidence: 99%